(untitled) (Medicine Today, 2023)
Introduction: There are many Hypertensive disorders in pregnancy like preeclampsia, eclampsia etc. Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Some studies have implicated that low serum calcium levels may have a role in pre-eclampsia but other studies failed to find relation between low levels of these trace elements and pre-eclampsia. Objectives:​To evaluate serum calcium in pre-eclampsia & non pregnant women. Materials and Methods: ​This cross sectional study was carried out in among 31 pre-eclampsia patients, aged 20 to 40 years, and gestational age ranges from 20 to40 weeks and 31 age matched normotensive non-pregnant women having no proteinuria. Serum calcium was measured by Colorimetric method. Results:The mean serum calcium level was 5.91 (±2.12) mg/dl in pre–eclampsia and was 5.72 (±2.46) mg/dl in normal women. Conclusion The mean serum calcium level did not differ significantly between the subjects of pre–eclampsia and normal women (t=0; p<.05). The means of both data sets are equal so we can conclude that there is no significant difference between them. Medicine Today 2023 Vol.35(2): 121-123